Synthesis and evaluations of selective COX-2 inhibitory effects: Benzo[d]thiazol analogs. Issue 17 (1st September 2020) - He, Li-Ya; Zhang, Shan-Shan; Peng, Ding-Xin; Guan, Li-Ping; Wang, Si-Hong
Graphical abstract: Abstract: A series of benzo[ d ]thiazole analogs were synthesized and evaluated for their anti-inflammatory and analgesic effects. Using an ear edema model, except for compounds 2k, 2m -2q and 3a, other compounds showed the anti-inflammatory effects. Among them, compounds 2c, 2d, and 2g showed the best anti-inflammatory activity (inhibition rate: 86.8%, 90.7% and 82.9%, respectively). By the acetic acid-induced abdominal writhing test, except for compounds 2e, 2l, 2m, 2o, 2p and 3a, other compounds showed the analgesic effects with inhibition rate values of 51.9–100% (2a-2r ) and 68.6–100% (3a-3g ). Next, compounds 2c, 2d, 2g, 3d, 3f, 3g that displayed the excellent anti-inflammatory and analgesic activities were evaluated for their inhibitory effect against ovine COX-1 and COX-2. Compounds 2c, 2d, 2g, 3d, 3f, 3g were weak inhibitors of the COX-1 isozyme but exhibited the moderate COX-2 isozyme inhibitory effects IC50 from 0.28 to 0.77 μM and COX-2 selectivity indexes (SI: 18.6 to 7.2). This benzo[ d ]thiazole moiety will be proved to be of great significance for developing more potent COX-2 inhibitors.